The difficulties of bimetallism - Bastable, C. F. (Statistical and Social Inquiry Society of Ireland, 1882)
There has been within the past few months a marked revival of the bimetallist agitation, that had for some time previously been declining under the, for it, unfavourable influences of expanding trade and industrial activity. Recent utterances of prominent public men have gained for this technical and obscure subject an amount of attention that no merely theoretical discussion could possibly excite, and hopes seem to be felt in some quarters that all the evils of depression would disappear if the expedient of an international double standard were only adopted. As the advocates of this scheme somewhat too hastily assume that all reason and experience, as well as the weight of competent opinion, are on their side, it may not be unfitting to briefly indicate some of the difficulties that hinder the acceptance either of bimetallism pure and simple, or any of the numerous half-way proposals as either sound in theory or likely to prove beneficial in practice.
Read Tuesday, 24th January, 1893
Keywords: Bimetallism; Coinage; 314.15